Riding paradox: Lessons learned from Italian participatory policy-making experiences - Mannarini, Terri (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
In this paper, some of the psychosocial aspects of participatory policy making in Italy are analyzed, with specific attention given to the relationship between internal agents (IAs) and external agents (EAs). Based both on a review of the documented Italian case studies in a variety of policy areas and on direct experience, three major issues are addressed: conflict, power and exclusion. It is argued that the majority of the problems that pertain to the relationship between IAs and EAs can be attributed to two comprehensive underlying dimensions that characterize all participatory policy-making processes, namely, the paradoxical nature of institutionalized participation and the tensive nature of social relationships. Implications for community work are discussed.